INSTITUTIONAL FORCES AND LIFE CYCLE STAGES OF WOMEN-LED SMEs IN DEVELOPING ECONOMIES - Kumudinei, D. (University of Jaffna, 2016)
Despite women`s enormous involvement in economic activities through Small and Mediumscale Enterprises (SMEs), their progress has been relativelyslow and the macro environmental influences impeding women-led SMEs have been numerous. These impediments vary at different life cycle stages of the women-led business. As informed by life cycle stage theories of organizations, the formation, establishment, continuation and growth stage of businesses each have their own characteristics and needs, and thus entail specific resource requirements to be fulfilled for proceed to the next stage and/or for ensuring survival. This knowledge builds reasonable certainty that the issues undergone by womenled SMEs may vary and be distinctive at diverse life cycle stages of their businesses. The institutional environment of a country can impose restrictions or facilitate growth of entrepreneurship and small businesses. Even though evidence on issues related to formation, establishment, continuity and growth of women-led SMEs are not rare in the existing literature, the impact of the institutional environment at various business life cycle stages have not been well investigated. Thus, the aim of this study is to examine the institutional forces that affect the businesses at diverse life cycle stages of women-led SMEs in developing economies. Drawing from the institutional theory, the present study examines the institutional environmental forces influencing women-led SMEs at different stages of the business life cycles. It develops several propositions, building relationships among three institutional forces and different life cycles stages passed by women-led SMEs. It examines the effects of regulatory, normative and cognitive dimensions of the institutional environment at developing economy contexts. Based on the previous research findings, it encapsulates how apex level environmental conditions of under-developed institutional environments affect the life course of grass-root level women-led SMEs. Concurrently, the findings shed light on which dimension(s) of the institutional environment are most significant at a distinctive stage of women-led SME.
Keywords: Institutional environment; Life cycle stages; SMEs; Women-led; Developing economies